2014
DOI: 10.1007/s10695-014-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and antioxidant enzyme activities in rainbow trout (Oncorhynchus mykiss) juveniles fed diets supplemented with sage, mint and thyme oils

Abstract: This study evaluated effects of dietary supplementation of sage (Salvia officinalis), mint (Mentha spicata) and thyme (Thymus vulgaris) oils on growth performance, lipid peroxidation level (melondialdehyde, MDA) and liver antioxidant enzyme activities (superoxide dismutase, SOD; catalase, CAT; glucose-6-phosphate dehydrogenase, G6PD; glutathione reductase, GR; glutathione-S-transferase, GST and glutathione peroxidase, GPx) in rainbow trout (Oncorhynchus mykiss) juveniles. For this purpose, triplicate groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 41 publications
(32 reference statements)
12
68
2
Order By: Relevance
“…Findings of our study shows that trout fed diets supplemented with T. vulgaris at 0.5-2 ml/kg feed demonstrated an enhancement in the growth performance, but the best results was seen in 0.5 ml/kg feed group. In their study by Sonmez et al (2015), when rainbow trout were fed diets containing thyme oils at 500, 1,000 and 1,500 mg/kg feed for 60 days illustrated a higher weight gain and SGR than the control group, indicating a positive efficacy of thyme oils on the improving of the nutrient utilization by fish. Also, Zaki, ALabib, Nour, Tonsy, and Mahmoud (2012) showed that tilapia (Oreochromis niloticus) fed with thyme at 1% and 2% demonstrated an improvement in the growth performance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Findings of our study shows that trout fed diets supplemented with T. vulgaris at 0.5-2 ml/kg feed demonstrated an enhancement in the growth performance, but the best results was seen in 0.5 ml/kg feed group. In their study by Sonmez et al (2015), when rainbow trout were fed diets containing thyme oils at 500, 1,000 and 1,500 mg/kg feed for 60 days illustrated a higher weight gain and SGR than the control group, indicating a positive efficacy of thyme oils on the improving of the nutrient utilization by fish. Also, Zaki, ALabib, Nour, Tonsy, and Mahmoud (2012) showed that tilapia (Oreochromis niloticus) fed with thyme at 1% and 2% demonstrated an improvement in the growth performance.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Hoseini and Yousefi (2018) demonstrated thyme extract at 5-20 g/kg feed suppressed AST and ALT levels in rainbow trout during 2 weeks experiment; and Zadmajid and Mohammadi (2017) measured a significant decrease in values of these enzymes in carp (Carassius auratus gibelio) with an increasing in dietary thyme oils up to 800 mg/kg feed. Rainbow trout fed with thyme oils at 500-1,500 mg/kg feed for 2 months exhibited an increase in some antioxidant activities in liver tissues (Sonmez et al, 2015). However, TA B L E 4 Growth performance of rainbow trout fed on diets containing essential oil of Thymus vulgaris at 0.5, 1 and 2 ml/kg feed for 60 days at 17°C microscopic evaluation of some fish tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…() and Sönmez et al . () reported a heating process (40°C) for 3 h, and then, the diet was top‐dressed with fish oil containing carvacrol by slowly mixing in a food mixer.…”
Section: Stability In Feedmentioning
confidence: 99%
“…were purchased from NURİ AGA LTD and added to a commercial trout extruded feed (Pınar™, Turkey) at a dose of 0.5, 1.0and 1.5 % by a mixer. The diets were prepared according to the previously described protocol (Sönmez et al, 2015).Mint, thyme and sage oils contained 74 g kg -1 pulegone, 77 g kg -1 carvacrol and 76 g kg -1 1,8-cineole, respectively. Control diet contained no herbal oil.…”
Section: Fish and Experimental Conditionmentioning
confidence: 99%